Lycoperoside H, a steroidal alkaloid saponin in tomato seeds, ameliorates atopic dermatitis‐like symptoms in IL‐33 transgenic mice - Takeda, Shogo; Miyasaka, Kenchi; Shimoda, Hiroshi (Journal of food biochemistry, 2021)
Tomato seeds contain steroidal saponins called lycoperosides. However, it currently remains unclear whether lycoperosides exert anti‐inflammatory or anti‐allergic effects. Therefore, we herein investigated the effects of tomato seed extract (TSE) and lycoperoside H (LH) in Interleukin (IL)‐33 transgenic mice. TSE (500 mg/kg) or LH (10 mg/kg) was orally administered once a day for 101 days and then evaluated mouse behavior, skin symptoms, and blood and skin inflammatory cytokines. TSE slightly suppressed scratching behavior, while TSE and LH both increased locomotive activity. LH also significantly suppressed inflammation scores in the limbs, and TSE and LH reduced transepidermal water loss. Epidermal hyperplasia and the accumulation of eosinophils and mast cells were decreased by TSE and LH. Skin Th2/Th1 cytokine ratio and serum IgE concentrations were significantly reduced by TSE and LH. The present results suggest that the oral administration of LH derived from tomato seeds effectively ameliorates the symptoms of atopic dermatitis. Practical applications It has been reported that tomato seeds contain steroidal saponins, lycoperosides, though the effects of lycoperosides on anti‐inflammatory or anti‐allergic have not yet been revealed. In this study, we demonstrated that the oral administration of lycoperoside H derived from tomato seeds suppressed atopic dermatitis symptoms in IL‐33 transgenic mice. Tomato seed extract (TSE) and lycoperoside H (LH) increased locomotive activity and suppressed scratching behavior caused by pruritus in interleukin‐33 transgenic mice. TSE and LH attenuated skin inflammation and reduced transepidermal water loss (TEWL). Amelioration of epidermal hyperplasia and the accumulation of eosinophils and mast cells were also observed. TSE and LH also reduced the skin Th2/Th1 cytokine ratio and serum IgE concentrations.